Optimasi Proses Evaluasi Belajar melalui Pengembangan Sistem Ujian Komputerisasi di SMP Negeri 2 Majene - Zulkifli, Zulkifli; KH, Musliadi; Ansar, Ansar; U, M Ikhsan (Journal of Digital Ecosystem for Natural Sustainability, 2025)
This study aims to develop and implement a computer-based semester exam information system at State Junior High School (SMP) 2 Majene to optimize the learning evaluation process. The background of this study is the still widely used manual exam system, which requires a significant amount of time and energy, and poses a risk to the efficiency and accuracy of the assessment. The method employed is Research and Development (R&D) with the ADDIE model approach, which comprises the stages of analysis, design, development, implementation, and evaluation. The system was developed using the PHP programming language and MySQL database with a client-server architecture. The data collection process was carried out through observation and interviews with teachers and education personnel. The implementation results showed that the system ran well, allowing teachers and operators to input questions, students to answer exams digitally, and exam results could be directly processed and printed quickly and accurately. User evaluations stated that this system was effective in increasing the efficiency of exam implementation and reducing administrative burdens. Thus, this information system is expected to be a technological solution that supports digital transformation in the elementary education environment.